Using Emergence to Take Social Innovation to Scale - and Wheatley, Margaret; Frieze, Deborah (The Shambhala Institute, 2007)
In spite of current ads and slogans, the world doesn’t change one person at a time. It changes as networks of relationships form among people who discover they share a common cause and vision of what’s possible. This is good news for those of us intent on changing the world and creating a positive future. Rather than worry about critical mass, our work is to foster critical connections. We don’t need to convince large numbers of people to change; instead, we need to connect with kindred spirits. Through these relationships, we will develop the new knowledge, practices, courage, and commitment that lead to broad-based change. But networks aren’t the whole story. As networks grow and transform into active, working communities of practice, we discover how Life truly changes, which is through emergence. When separate, local efforts connect with each other as networks, then strengthen as communities of practice, suddenly and surprisingly a new system emerges at a greater level of scale. This system of influence possesses qualities and capacities that were unknown in the individuals. It isn’t that they were hidden; they simply don’t exist until the system emerges. They are properties of the system, not the individual, but once there, individuals possess them. And the system that emerges always possesses greater power and influence than is possible through planned, incremental change. Emergence is how Life creates radical change and takes things to scale. Emergence has a life-cycle. It begins with networks, shifts to intentional communities of practice and evolves into powerful systems capable of global influence. Since its inception in 1992, The Berkana Institute has striven to learn how living systems work, how they emerge from networks to communities to systems of influence. In our global work—primarily with economically poor communities in many different nations—we have experimented actively with emergence in many different contexts. We have demonstrated what’s possible when we connect people across difference and distance. By applying the lessons of living systems and working intentionally with emergence and its life-cycle, we have become confident that local social innovations can be taken to scale and provide solutions to many of the world’s most intractable issues.